Pengaruh Kompetensi, Independensi, Dan MotivasiAuditor Terhadap Kualitas Audit (Studi Empiris PadaKAP di Surakarta dan Yogyakarta) - Zulian, Ketri Saputri, Dra. Nursiam, M.H., Ak., CA (2016)
The purpose of this study was to examine the effect of the competence, independence and motivation auditor to audit quality. Samples were working in Public Accountant Office in Surakarta and Yogyakarta. The sampling technique used convanience sampling. Data were obtained from questionnaires with the amount of data as much as 35 respondents from seven public accounting firm. Data were analyzed using statistical descriptions of testing, testing instrument data and classic assumption test before hypothesis test. Hypothesis testing in this study using multiple linear regression analysis with t test, test F and test R2. The results of this study indicate that the variable competence of auditors, auditor independence and auditor motivational have effect on audit quality.